Combining ability of extra-early maturing provitamin A maize (Zea mays L.) inbred lines and performance of derived hybrids under Striga hermonthica infestation and low soil nitrogen - Makinde, S.A.; Badu-Apraku, B.; Ariyo, O.J.; Porbeni, J.B. (2023)
Low soil nitrogen (low-N), Striga hermonthica infestation and vitamin A deficiency in normal endosperm maize are major challenges confronting maize production and nutrition of the people of sub-Saharan Africa (SSA). Development of pro-vitamin A (PVA) maize hybrids with combined resistance/tolerance to the two stress factors is crucial in mitigating the food insecurity and nutrition challenges resulting from low-N deficiency and Striga infestation. One hundred and fifty hybrids plus six hybrid checks were evaluated under low-N, Striga-infested and optimal conditions in Nigeria for two years. The study examined the combining ability of the PVA inbreds in contrasting environments, classified them into heterotic groups, examined the inter-relationships of grain yield and other agronomic traits of the inbreds in hybrid combinations and assessed the performance and stability of the PVA hybrids across environments. Additive gene action conditioned the inheritance of grain yield under Striga infestation and optimal conditions while non-additive gene action played the major role in the inheritance of grain yield under low-N. Hybrids TZEEIOR 217 × TZEEIOR 197 and TZEEIOR 245 × TZEEIOR 195 were the top-yielding under Striga and low-N conditions, respectively. Inbred lines were classified into three heterotic groups. Inbreds TZEEIOR 195 and TZEEIOR 221 were identified as testers while TZEEIOR 197 × TZEEIOR 82, TZEEIOR 132 × TZEEIOR 195 and TZEEIOR 205 × TZEEIOR 221 were identified as single-cross testers. Ear aspect had direct contribution to grain yield, justifying its inclusion in the multiple trait base index used for selection of Striga resistant and low-N tolerant maize genotypes in SSA. Hybrids TZEEIOR 195 × TZEEIOR 149, TZEEIOR 195 × TZEEIOR 150, TZEEIOR 245 × TZEEIOR 195, TZEEIOR 30 × TZEEIOR 150 and TZEEIOR 245 × TZEEIOR 30 were high-yielding and stable across test environments. These hybrids should be tested extensively in on-farm trials and commercialized to contribute to food security in SSA.